On the Development of Christian Medical Services in Modern Shandong and Their Social Impact - WANG Zheng, (Journal of Research for Christianity in China (JRCC), 2025)
After the Second Opium War, missionaries were permitted to enter China's interior to spread their faith. Western Protestant missionaries began arriving in Shandong in large numbers to conduct missionary work. They traveled throughout the province preaching, building churches, and carrying out evangelistic activities, with medical services being one of their key focuses. This was done both to safeguard the health of the missionaries and their families, and to better facilitate their missionary endeavors. Protestant medical services flourished in Shandong, ranking among the most advanced in the country. Shandong led the nation in the number of church-run hospitals, foreign doctors and nurses, salaried Chinese doctors and nurses, and hospital beds. Protestant missionary societies established numerous well-equipped, large-scale hospitals in Shandong, such as the Weishi Boji Hospital in Dexian, the Guangren Hospital in Pingyin, the Meitie Hospital in Yexian, and the Huailin Hospital in Huangxian. Furthermore, Protestant missionary societies across Shandong jointly founded a church-affiliated university—Qilu University. Its medical school enjoyed an exceptionally high reputation nationwide, cultivating a large number of outstanding medical professionals for the advancement of Christian healthcare.
Keywords: Churches; Medical Endeavors; Modern Shandong; Social Development